Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1155/2014/534904
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Amiodarone-Induced Thyrotoxicosis and Associated Risk Factors in Japanese Patients

Abstract: Amiodarone is a widely used agent for life-threatening arrhythmias. Although amiodarone-induced thyrotoxicosis (AIT) is a major adverse effect that can cause recurrence of arrhythmias and exacerbation of heart failure, risk factors for AIT among amiodarone-treated Japanese patients have not been elucidated. Here, we investigated the prevalence and predictive factors for AIT. The study subjects were 225 patients treated with amiodarone between 2008 and 2012, who were euthyroid before amiodarone therapy. All pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 21 publications
1
10
1
8
Order By: Relevance
“…Consequently, a younger age at the initiation of amiodarone, DCM, and cardiac sarcoidosis were identified as independent risk factors for the development of amiodarone‐induced hyperthyroidism. Previous studies suggested that young age is a risk factor for amiodarone‐induced hyperthyroidism [12,13,19,35], and our results are consistent with these studies. Although, we cannot conclude that age at the initiation of amiodarone therapy was a clinically significant risk factor for amiodarone‐induced hyperthyroidism in the present study, given both the low sample size and the small effect size of the odds ratio.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Consequently, a younger age at the initiation of amiodarone, DCM, and cardiac sarcoidosis were identified as independent risk factors for the development of amiodarone‐induced hyperthyroidism. Previous studies suggested that young age is a risk factor for amiodarone‐induced hyperthyroidism [12,13,19,35], and our results are consistent with these studies. Although, we cannot conclude that age at the initiation of amiodarone therapy was a clinically significant risk factor for amiodarone‐induced hyperthyroidism in the present study, given both the low sample size and the small effect size of the odds ratio.…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of amiodarone‐induced hyperthyroidism was higher in our study than in previous studies conducted in Asian countries [13,19,35] that included only patients with euthyroidism. The prevalence of amiodarone‐induced hyperthyroidism was previously reported to be 4.0% in Taiwan [19] and 6% in the Chinese population living in Hong Kong [13].…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Amiodarone-induced thyrotoxicosis (AIT) has been associated with increased mortality in older individuals with impaired ventricular function [1], underlying the importance of rapid restoration and maintenance of euthyroidism in this condition. Amiodarone has been reported to cause thyroid dysfunction in 15-20% of cases [1][2][3], with the incidence of thyrotoxicosis being approximately 5% [3,4]. Plasmapheresis as a treatment option for thyrotoxicosis refractory to medical therapy has shown mixed results.…”
Section: Introductionmentioning
confidence: 99%